The Views of Nahdlatul Ulama Leaders on the Problem of Saweran to Qori'ah - Sulaiman, Agus; Nasrulloh, Nasrulloh (The Institute of Research and Service Community IPMAFA Pati, 2023)
This article aims to provide an in-depth understanding of Nahdlatul Ulama figures and their influence on the phenomenon of saweran (giving money or gifts) to Qori'ah (Qur'an reciters) in various religious events. The article aims to convey the views of Islamic scholars regarding the legal, ethical, and social impact aspects of this practice, as well as provide a perspective that can provide solutions to the problems that occur. Nahdlatul Ulama (NU) is one of Indonesia's most prominent Islamic organizations, which significantly influences the development of Islam in Indonesia. The data was collected qualitatively by looking at primary sources of Nahdlatul Ulama media, including websites, applications, social media, and secondary sources from other media that also reported on the views of Nahdlatul Ulama figures. The data taken is comprehensive, where the researcher tries to take all existing data objectively so that valid data processing is produced. The theory presented in this article comes from the books of classical and contemporary scholars related to the discussion. The results of this study indicate that the views of Nahdlatul Ulama (NU) leaders had succeeded in becoming a warning and advice for the people of Indonesia to abandon the saweran tradition against Qori'ah because it is not by social norms and violates the manners and ethics in Islam when recited the holy verses of the Qur'an.